(untitled) (African Journal of Biomedical Research, 2024)
Several bioactive principles of plant extracts exhibit poor absorption and bioavailability due to their high molecular size or poor aqueous solubility. Nanoformulations of herbal drugs have emerged as essential tools to enhance bioavailability, solubility, drug retention time, and delivery while minimizing toxic effects. This can potentially strengthen the action of herbal extracts, reduce dosage and side effects, and improve bioactivity. The purpose of this study was to evaluate the radical scavenging activity of nanosuspension of Annona muricata leaf extract and quantify its phytoconstituents using a gas chromatography-flame ionization detector (GC-FID). Extraction of crude extract and quantification of phytochemicals by GC-FID was done. The in vitro antioxidant activity of the crude extract and nanosuspension of Annona muricata were evaluated using the DPPH scavenging activity and the ferric reducing antioxidant power (FRAP). The particle size analysis of the nanosuspension showed that particles were in the nano-range with average particle size of 73.35 nm and polydispersity index (PDI) of 0.404. The results also revealed that the nanoformulation augmented the antioxidant potentials of the crude extract of Annona muricata. At a concentration of 20 mg/ml, the percentage scavenging activity increased significantly (p < 0.05) from 71.24% for crude to 95.39% for nanosuspension, even higher than ascorbic acid (standard) which stood at 82.36%. Annona muricata is a powerful antioxidant agent and the use of nanotechnology can resolve some of the inherent biopharmaceutical shortcomings of herbal materials and serve as a tool for optimizing the bioactivity of the active components of plant extracts in herbal formulation.